2017
DOI: 10.1159/000480635
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Characteristics and Prognostic Analysis of Status Epilepticus in Northeast China

Abstract: Objective: Status epilepticus (SE) is a neurological emergency that may cause severe neurological deficiency and even death. The aim of this study was to analyze the clinical characteristics and prognosis of SE in northeast China. Additionally, the etiology and classification are discussed. Materials and Methods: We retrospectively collected the clinical profiles of patients diagnosed with SE in the Epilepsy Center of Jilin University between January 2011 and May 2015. The causes and clinical courses were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Several studies have, however, reported lower mortality rates in the Chinese population. Our findings are consistent with those from a retrospective hospital-based study in Jilin province, which reported an overall mortality of 6.7% [13]. In a study from Sichuan, a 1.5% mortality rate in people with non-refractory SE, with an overall mortality of 7.14% in all people with SE [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have, however, reported lower mortality rates in the Chinese population. Our findings are consistent with those from a retrospective hospital-based study in Jilin province, which reported an overall mortality of 6.7% [13]. In a study from Sichuan, a 1.5% mortality rate in people with non-refractory SE, with an overall mortality of 7.14% in all people with SE [14].…”
Section: Discussionsupporting
confidence: 91%
“…Acute symptomatic causes which are frequently identified (up to 61.4%) as the main aetiology of SE [22] were not considered. These mainly include central nervous system infection, stroke or autoimmune encephalitis [9,13,22], and apparently serve as the main drivers of SE-related death [23]. The current search strategy is therefore likely to have missed people with severe SE or those who died in whom the direct cause was listed as the primary diagnosis and not as SE.…”
Section: Discussionmentioning
confidence: 99%